Examination of Upper Extremity Length Discrepancy in Patients with Obstetric Brachial Plexus Paralysis - Murat Danisman; Abdulsamet Emet; Ismail Aykut Kocyigit; Ercan Hassa; Akin Uzumcugil (MDPI AG, 2023)
Since the natural course of obstetric brachial plexus palsy is variable, several problems are encountered. One important question, in considering patients with OBPP under observation in outpatient clinical settings, is whether children will have length discrepancies in their arms. The aim of this study was to determine differences in the length of the affected extremity, in comparison to the opposite upper extremity. As such, 45 patients, aged 6 months to 18 years, with unilateral brachial plexus palsy developed due to obstetric reasons, were included in the study. Affected and healthy side humerus, ulna, radius, 2nd metacarpal and 5th metacarpal lengths were evaluated according to gender, age, side, Narakas classification, primary and secondary surgery. Statistically significant differences were found in the change rates of affected/healthy humerus, radius, 2nd metacarpal and 5th metacarpal lengths according to age (93%, 95%, 92%, 90% and 90%, respectively). Affected/healthy change rates of ulna, radius, 2nd metacarpal and 5th metacarpal lengths were found to differ statistically (p < 0.05) according to the Narakas classification variable (94%, 92%, 95%, 94% and 94%, respectively). There were no statistically significant differences in the ratios of affected/healthy change in the lengths of the humerus, ulna, radius and 5th metacarpal compared to the primary surgery (p > 0.05). The ratios of affected/healthy change in ulna, radius and 5th metacarpal lengths were found to differ statistically (p < 0.05) according to secondary surgeries (93%, 91%, 91% and 92%, respectively). Joint and bone deformities and bone shortening were observed after changes that occurred in the postnatal and growing periods due to obstetric brachial plexus palsy. Every increase in function to be gained in the upper extremity musculature was also potentially able to reduce problems, such as shortness.